A variabilidade da frequência cardíaca como indicador de estresse e de risco cardiovascular em adultos assintomáticos - Bianchim, Mayara Silveira [UNIFESP] (2015)
Cardiovascular diseases (CVD) are the leading cause of death worldwide. Risk factors stratification is crucial for the prevention and treatment of cardiovascular diseases. Stress and autonomic imbalance are among the most fundamental factors for the CVD installation. Autonomic imbalance causes low heart rate variability (HRV), as others effects. The HRV is a simple and low cost tool to measure the autonomic modulation to the heart, and has influence of stress. In this context, this study proposed the use of HRV as a stress indicator and the proper establishment of the relationship between each HRV index with stress indicators adjusted for other risk factors. Therefore, the anthropometric characteristics, blood glucose and lipids, salivary cortisol concentration, HRV, lung function by spirometry, physical fitness by cardiopulmonary exercise test and daily physical activity by accelerometry were analyzed. The study included 94 asymptomatic volunteers aged 48-78 year-old. Some HRV indexes were identified by linear regression analysis, as predictors of salivary cortisol concentration and perceived stress in asymptomatic adults and elderly, even after adjusting for age, sex and other risk factors. In a multiple regression analyses salivary concentrations of cortisol were negatively correlated with the indices RMSSD (?: -1.193), sample entropy (?: -0.691), SDRR (?: -0.275), and HF (-0.339); and perceived stress with LF (?: -0.258). Concluding, an association between stress and low HRV was identified in the present study, regardless of age, sex and risk factors for CVD.